ENCAPSULATION OF PARTIALLY PURIFIED BROMELAIN FROM PINEAPPLE CORES IN ALGINATE-PECTIN BEADS AS A TARGETED ANTIPLATELET AGENT - PRABOWO, HEGI ADI; BUDIANTO, EMIL; HUDIYONO, SUMI (International Journal of Applied Pharmaceutics, 2021)
Objective: Oral administration of bromelain can decrease its bioactivity once it makes contact with stomach acid. Therefore, bromelain was loaded into alginate (Alg), pectin (Pec), and alginate-pectin (AP) beads to control its release into the intestines and avoid degradation. Methods: Crude bromelain was purified by ammonium sulfate precipitation and the dialysis process. In vitro releases and kinetics studies of bromelain-loaded alginate-pectin beads were carried out using an acid and phosphate buffer medium. The beads were characterized using physical analysis, Fourier-Transform Infrared Spectroscopy (FTIR) analysis, and Differential Scanning Calorimetry (DSC) analysis. Results: The dialysis fraction of bromelain has a specific activity of 67.93 U/mg, 3.05 times that of crude bromelain. That fraction was encapsulated in Alg, Pec, and AP beads with a range of encapsulation efficiency around 82.70–91.39%. Bromelain-loaded pectin and AP19 beads were chosen to study in an in vitro release based on their swelling properties and encapsulation efficiency. Bromelain-loaded AP19 beads have lower release than bromelain-loaded pectin beads in both dissolution mediums. The cumulative releases of AP19 are 9.99 and 87.81% in 0.1 N HCl and phosphate buffer medium, respectively. Bromelain-loaded P and AP beads both follow the zero-order kinetics model and the dissolution mechanism of the beads is non-Fickian with a combination of diffusion and erosion. The in vitro antiplatelet activity of dissolution aliquots (20.51 and 18.48%) is lower than its dialysis fraction (56.04%). Conclusion: This in vitro research data shows promising potency for AP as a carrier for oral administration of bromelain as an antiplatelet agent.